A Meandered Triple-band Dipole Antenna with 920 MHz Artificial Magnetic Conductor - Abu, Maisarah; A. Rahim, Mohamad Kamal (2010)
A meandered triple-band dipole antenna integrated with 920 MHz Artificial Magnetic Conductor (AMC) is presented. The AMC structure is called a high-impedance surface (HIS) structure and is useful as a ground plane to the antenna. This structure can be used to prevent the degradation of tag and antenna performance caused by the conductive materials (metal objects) and to increase the antenna gain.